A BWM approach to determinants of sustainable entrepreneurship in small and medium-sized enterprises - Mendes, A. (2022)
Small and medium-sized enterprises (SMEs) constitute an extremely large percentage of most nations’ businesses. These companies are also expressing growing concerns about sustainability and its strategic integration into operations. However, SMEs have been prevented from making investments in sustainability by the absence of a holistic view of this topic, an overemphasis on an economic perspective, and the consequent devaluation of environmental and social perspectives. In this context, greater importance needs to be given to investigating SME sustainability and building a transparent, holistic, and realistic business model. The present study combines cognitive mapping and the best worst method (BWM) to identify determinants of sustainable entrepreneurship in SMEs. These techniques were applied in two meetings with a panel of specialists with knowledge about and experience in this subject matter. The insights obtained during the two panel meetings allowed the proposed process-oriented approach to assist decision-makers in analyzing a sample of SMEs and selecting the ones that best match the following clusters of decision criteria: (1) entrepreneur profile; (2) firm internal characteristics; (3) economic factors; (4) other external factors; and (5) market. The results were validated by four representatives of the Portuguese Institute for Small and Medium-sized Enterprises and Innovation (Instituto de Apoio às Pequenas e Médias Empresas e à Inovação (IAPMEI) in Portuguese). The study’s contributions and limitations are also discussed.